A leveza dos aforismos de "I pensieri di Bellavista" - Silva, Clodoaldo Vicente da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
I pensieri di Bellavista é uma obra de Luciano De Crescenzo, autor contemporâneo italiano, composta de 365 aforismos. Estes aforismos são dotados de magnífica leveza e profundidade. Para atingir esse efeito de leveza, De Crescenzo se vale do conhecimento acumulado em sua carreira como romancista, filósofo, humorista, cineasta e cidadão napolitano. Além disso, recorre à ironia, figura de linguagem que, por mais de uma via, incorporou-se à cultura napolitana. Recursos como a sátira e o humor também apoiam as breves narrativas na voz do professor Don Gennaro Bellavista. Não apenas recursos linguísticos amparam De Crescenzo na construção da egrégora de leveza que envolve esta obra, o autor também se vale da filosofia Epicurista, dos valores do taoismo clássico e da própria cultura do povo napolitano nesta construção. O presente estudo verifica como são construídos os aforismos, em sua maioria, na estruturação linguística e semântica, para investigar como é criado o efeito de leveza em cada um deles.

I pensieri di Bellavista is a work of Luciano De Crescenzo, contemporary italian author, composed of 365 aphorisms. These aphorisms are endowed with magnificent lightness and profundity. In order to reach such lightness effect, De Crescenzo summons his knowledge, accumulated through his novelist, philosopher, humorist and film maker careers, as well through his Neapolitan citizenship. Besides that, he resorts to irony, figure of speech which, through various ways, had integrated itself to the Neapolitan culture. Means such as satire and humor also supports the brief narratives in the speech of professor Don Gennaro Bellavista. Not only linguistic means are summoned to ground De Crescenzo in the building of the lightness mood that involves this work, the author also evokes the Epicurean philosophy, the classic Taoist values and the Neapolitan culture itself to the same purpose. The present research verifies how the aphorisms are constructed, mostly, in the linguistic and semantic structuration, to investigate how the lightness effect in each of them is created.
The lightness of the aphorisms of "I pensieri di Bellavista"
Keywords: Leveza; Amor; Ironia; Sátira; Humor; Filosofia; Epicurismo; Taoísmo; De Crescenzo; Love; Irony; Satire; Philosophy; Epicureanism; Taoism